PREVALENCE OF CYP2D6*4 GENOTYPE AND ITS ASSOCIATION WITH TAMOXIFEN INDUCED HOTFLASHES IN PAKISTANI FEMALE BREAST CANCER PATIENTS - Nazir, Nusrat; Waheed, Akbar; Farhat, Kulsoom; Ismail, Muhammad; Mansoor, Qaisar; Qazi, Noreen (Journal of Postgraduate Medical Institute, 2015)
Objective: To investigate the frequency of CYP2D6*4 in Pakistani breast cancerpatients for the first time and also investigate its association with tamoxifeninduced hot flashes. Methodology: A retrospective study carried out in Nuclear Medicine, Oncologyand Radiotherapy Institute (NORI) Islamabad and Combined Military Hospital Rawalpindi (CMH). Pre and postmenopausal breast cancer womenwho were advised 20mg/day of tamoxifen as adjuvant therapy were recruitedfor the study. The data from January 2000 to September 2013 was collected from the medical records of the outpatient breast cancer clinics. 232 womenwho fulfilled the eligibility criteria were initially recruited and their peripheral whole blood samples were taken. CYP2D6*4 was determined by using PCRRFLP, allele*4 was not identified in 9 women and study was conducted on 223women. None of the women died during the study period. Results: Data of 223 women was analysed and the allele frequency of CYP2D6*1 was 86% and that of CYP2D6*4 was14 %. Women with CYP2D6*4/*4did not experience mild to moderate or severe hot flashes as compared towomen heterozygous or homozygous for wild type allele *1. Conclusion: The frequency of CYP2D6*4 allele in Pakistani breast cancerwomen is 14% which is comparable to the Caucasians moreover CYP2D6*4/*4 genotypes have lower incidence of hot flashes, but the results are not statistically significant.